Strengthening Onion Cracker Production Technology at UD. Kalirejo Banyuwangi - Herdiana Dyah Susanti; Dian Arief Pradana (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2022)
The Banyuwangi Regency Government is currently trying to develop the tourism potential of Banyuwangi to introduce a variety of typical Banyuwangi souvenirs outside the region, one of which is crackers so that they are increasingly known throughout Indonesia and even abroad. The SMEs that have the potential to develop their products are UKM UD. Kalirejo which produces onion crackers. The specific targets in this activity are 1) partners can reduce defective products produced by incubation of automatic cracker cutting machine technology, 2) partners can use automatic cracker cutting machine technology, 3) open new marketing networks, 4) improve the quality of human resources through training on quality control management and quality control of raw materials, 5) academically, this activity can produce scientific articles published in national scientific journals. The methods used in this activity are 1) Training and Coaching, 2) Incubating Appropriate Technology Innovations, 3) Monitoring and Evaluation (MonEv) Activities. The results achieved were facilitation of repairing cracker production sites in accordance with industry standards, as well as facilitation of tools and machines for processing the scale of Appropriate Technology in the form of automatic cracker cutting machines.